A Review on the Decadal Irrigation System of Shali Water Reservoir. Issue 1 (July 2020) - Halder, S; Das, S; Basu, S
Abstract: Irrigation is a prime factor for agriculture, fishing and afforestation in two water scant districts namely Bankura and Purulia of West Bengal province in India. To fulfill such purposes, Shali reservoir was erected on the Shali River near Bhairabpur village of Gangajalghati block at Bankura district in 1978. After the four decades of construction it was found that only a few studies were conducted by previous researchers on Shali reservoir. In these four decades many things like population, climate, soil type, reservoir life, hydro-meteorological parameters like rainfall pattern, evaporation rates etc., people's behavior on water utilizations, river morphology -have been changed over periods. Therefore it is most needed to bring together all those previous researches for finding out the new need of any further detail research on Shali reservoir. This paper aims to coalesce all those researches in a succinct manner for the benefit of the people of Gangajalghati block in Bankura.